Corporate Governance and Stock Liquidity in Australia: A Pitch - Searat Ali (Journal of Accounting and Management Information Systems (JAMIS), 2016)
This pitch research letter (PRL) applies the pitch template developed by Faff (2015a) to an academic project in corporate finance; that is, corporate governance and market microstructure, namely, stock liquidity for Australian firms. The pitch template is useful in identifying the core elements that form the framework of research project. This PRL encloses a brief background about the pitcher and pitch, followed by a brief commentary on the pitch and personal reflections of the pitcher on the pitch exercise itself.
Keywords: G12; G34; 650; Pitching research; corporate governance; stock liquidity; Australia